Rancang Bangun Sistem Layanan Pelanggan (Customer Service) Berbasis Chatbot AI Pada INET Komputer - Indri Agustari; Evi Yulianingsih (BETRIK, 2026)
The rapid development of digital technology encourages educational institutions to improve the quality of information and administrative services. INET Komputer, as a training and technology course institution, faces challenges related to the high volume of customer inquiries that still rely on administrators, resulting in delayed responses and inefficiency in services. This study aims to design and implement an Artificial Intelligence (AI)-based customer service chatbot integrated with WhatsApp Business. The system development method used is the System Development Life Cycle (SDLC), which includes the stages of requirements analysis, system design, implementation, and testing. The chatbot was developed using the no-code platform ALATWA with a structured conversation flow design. The testing method used is Black Box Testing involving 5 respondents who acted as users to evaluate the chatbot performance through predefined conversation scenarios. The results show that the chatbot is able to provide automatic responses that are fast, consistent, and appropriate to user inputs related to class information, schedules, fees, and registration. The implementation of this chatbot has proven to improve administrative service efficiency and reduce the workload of administrators at INET Komputer.